Beyond Professional Boundaries: Managerial Leadership in Health Organizations Beyond the Medical Professio - Naufal, Ahmad (BKM Public Health and Community Medicine, 2024)
Purpose: This study aims to evaluate the traditional dominance of the medical profession in health organization management and highlight the need for a paradigm shift towards assessing leaders based on strong managerial competencies, independent of their professional background. Methods: Significant changes in the health sector, such as the enactment of Law No. 17 of 2023 on Health, mark a progressive step towards diversifying leadership in health organizations. A key aspect of this change is the reduction of the traditional dominance of the medical profession in managerial roles. There is a global trend indicating a decline in the dominance of the medical profession and an increase in the authority of other health professions such as nurses, pharmacists, and other health practitioners in clinical management and decision-making. This shift has led to the emergence of more specific disciplines such as health economics, health policy and management, and hospital management. This situation has resulted in doctors no longer occupying a dominant position in all aspects of healthcare. Results: Previous research indicates that leadership performance is not solely dependent on a medical background but on strong managerial competencies. Although it cannot be conclusively stated whether the best leaders come from medical or non-medical backgrounds, it is believed that doctors with additional managerial education can lead organizations better. Therefore, the selection of health organization leaders should focus on managerial skills rather than being confined to the medical profession. Conclusion: Health organizations that are reluctant to adapt to this change risk falling behind. According to Ecological Theory, only organizations that can adapt to environmental changes will survive and thrive, following the principle of "survival of the fittest." Thus, selecting leaders based on managerial competencies is crucial for the future of better healthcare services in Indonesia.